Full-scale fire test on a high-rise RC wall. (15th January 2021) - Pham, Duc Toan; Pinoteau, Nicolas; Yang, Mingguan; de Buhan, Patrick; Pimienta, Pierre; Mège, Romain
Highlights: The full-scale fire resistance test has been successfully carried out on an 8.4 m-high wall. The experimental results showed a large deflection of the high wall in fire conditions. Theoretical and numerical predictions appear to be in a good agreement with experimental results. Abstract: This paper describes a full-scale test carried out on a high-rise reinforced concrete wall subjected to fire loading conditions in the special Vulcain furnace (very large and modular gas furnace) at CSTB, France. The test sample was designed to represent a slender wall with a very large height/thickness ratio. The experimental results showed a large deflection of the high wall in fire conditions (almost equal to the wall height/24) even for a fire exposure time of 90 min. Such a deflection was significantly higher than the maximum value recommended by design codes (about the wall height/30 for 120 min of fire exposure). Furthermore, other test results (full-field displacements in the 3 directions, residual deformed shape after the heating and cooling phases) may also provide additional useful experimental data for validating available or future models (which are usually based on some specific assumptions). In addition, the measurements of thermal-induced deformed shape of the wall are compared to those predicted by an analytical solution derived from a simplified one-dimensional (1D) beam model, as well as to those obtained from non-linear finite-element simulations (with 2D plate elements), in order to assess the practical applicability of these simulations. These comparisons show a reasonably good agreement between the experimental results and the predictions of these models, thereby providing a first validation of the latter.